Evaluating Training and Apprenticeship as Non-Formal Education at International Manpower Development Japan - Waryono, Edi; Ahmad, Masduki; Rahmawati, Desi (Jurnal Paedagogy, 2023)
This study aims to analyze the evaluation results of the implementation of training and apprenticeships at IM Japan. This study used a qualitative approach using the CIPP (context, input, process, and product) model. The number of participants was 150 from Bekasi, West Java, Lampung, and Central Java. Data collection techniques used observation, interviews, and documents. Data analysis in this study went through data reduction, data presentation, discussion, and conclusion. The findings showed that the context and input aspects were considered quite good, with a percentage value of 22% each; the process aspect was considered very good, with a percentage rate of 49%, and the product aspect must be improved in alumni associations so that they could develop networks for alumni or participants training and apprenticeship related to workforce needs. The results of this study have implications that the process of non-formal education is an essential support for students, especially students in vocational schools so that their skills are qualified and meet the quality targets of the business world.